Cariniana pyriformis Miers growth in two light environments in Antioquia, Colombia (2019)
Cariniana pyriformis is a valuable forest species in South America wood market. Its wood is appreciated for its durability and versatility and used for sawn timber, veneer, light and heavy construction and furniture manufacture. Very few plantations of the species are established in Colombia. The species is harvested in natural forests, in spite of being in critical danger of extinction (Cardenas & Salinas, 2006). There is a substantial lack of information about the growth of Neotropical forest species which constitutes the first steps to develop the fprestry sector.